MANAJEMEN PEMERINTAHAN DINAS TENAGA KERJA KOTA PEKANBARU DALAM PENYELENGGARAAN TENAGA KERJA TAHUN 2014 - Yuni Erika; Wan Asrida (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
The aimed of this study to seeing how management of government Offices ofManpower in the operation of workforce in 2014. As for what is meant bymanagement of government is the process of government activity which is generallyassociated with effort to exercise the power of government by implementingmanagement functions consisting of planning, organizing, directing, coordinatingand controlling. This study used qualitative research methods with a descriptiveresearch can be interpreted as troubleshooters which described by describingsituation the subject of research with the facts visible and then connected using theexisting theories.The results of research showed that management of government Offices ofManpower in the operation of labor in 2014 is already well underway. Of theplanning process, Offices of Manpower prepare and make a program based on theneeds of the Pekanbaru’s workforce. In terms of organizing, every employee Officesof Manpower has been working in accordance with his duties. In the directing,Offices of Manpower implementing the program has been run in accordance withterm of reference. In term of coordination, Offices of Manpower in collaboration withPrivate Employment Training Institute and have good mutual relations. And the lastis controlling, Offices of Manpower go direcly monitor the extent of success of theprogram.In this research, budget constraints, limited education job seekers, limitedfacilities and infrastructure and than less participation job seekers becoming aproblem of Offices of Manpower in reducing unemployment.Keywords : Management of Government, Offices of Manpower, Manpower, Unemployment